Liver grafts procured from donors after circulatory death have no increased risk of microthrombi formation. Issue 12 (December 2016) - Verhoeven, Cornelia J.; Simon, Tiarah C.; de Jonge, Jeroen; Doukas, Michael; Biermann, Katharina; Metselaar, Herold J.; Ijzermans, Jan N. M.; Polak, Wojciech G.
Abstract : Microthrombi formation provoked by warm ischemia and vascular stasis is thought to increase the risk of nonanastomotic strictures (NAS) in liver grafts obtained by donation after circulatory death (DCD). Therefore, potentially harmful intraoperative thrombolytic therapy has been suggested as a preventive strategy against NAS. Here, we investigated whether there is histological evidence of microthrombi formation during graft preservation or directly after reperfusion in DCD livers and the development of NAS. Liver biopsies collected at different time points during graft preservation and after reperfusion were triple‐stained with hematoxylin‐eosin (H & E), von Willebrand factor VIII (VWF), and Fibrin Lendrum (FL) to evaluate the presence of microthrombi. In a first series of 282 sections obtained from multiple liver segments of discarded DCD grafts, microthrombi were only present in 1%‐3% of the VWF stainings, without evidence of thrombus formation in paired H & E and FL stainings. Additionally, analysis of 132 sections obtained from matched, transplanted donation after brain death and DCD grafts showed no difference in microthrombi formation (11.3% versus 3.3% respectively; P  = 0.082), and no relation to the development of NAS ( P  = 0.73). Furthermore, no microthrombi were present in perioperative biopsies in recipients who developed early hepatic artery thrombosis. Finally, the presence of microthrombi did not differ before or after additional flushing of the graft with preservation solution. In conclusion, the results of our study derogate from the hypothesis that DCD livers have an increased tendency to form microthrombi. It weakens the explanation that microthrombi formation is a main causal factor in the development of NAS in DCD and that recipients could benefit from intraoperative thrombolytic therapy to prevent NAS following liver transplantation. Liver Transplantation 22 1676–1687 2016 AASLD .